PENGARUH MAZHAB YIN YANG PAOAARSITEKTUR RUMAH TINGGAL KUNO CHINA 01 LASEM (The Influence of Yin Yang School of Thought towards the Architecture of Chinese's Old Residential Buildings at Lasem) - Djoko Darmawan (Unika Soegijapranata Semarang, 2012)
The study on the influence of Yin Yang School of Thought to the architectural design of Chinese's residence at Lasem aims to unravel the relationship between philosophy and the architectural buildings within the residential area. This study Is expected to provide benefits for the understanding of a design In Chinatown and to be a stimulus for further studies. The main problem is how to get the relationship between Yin Yang as one of the Chinese philosophical school of thoughts on one side and architectural design as the other side In Imposing an architectural product. The question Is whether there is a relationship between Yin Yang school of thought and architectural design of Chinese community's residence at Lasem, Central Java, viewed from some architectural elements, namely: plan and structure. Holistic analysis was used in this study and it viewed an object In the frame of a cultural. It means that a Chinese's object or architectural building as manifestation of cultural system, which consists of the concepts of Yin Yang, Chi and Wu Hslng. Further, this study covers three perspectives of philosophy, that is: philosophy as a science, philosophy as the way of thinking, and philosophy as the way of life, in the relation with architectural design of Chinese's community in Lasem.